Peran Dinas Lingkungan Hidup Dalam Mengatasi Pembuangan Sampah Sembarangan Oleh Masyarakat di Kota Tanjungpinang - Sofianto Sofianto; Aditya Saputra; Mellyana Candra (Jurnal Relasi Publik, 2024)
In Tanjungpinang City, there are several piles of waste from household production located on the roadside. Not only waste from household production, but also waste that is left over from building materials. The accumulation of garbage on the roadside of Tanjungpinang City is increasingly unstoppable and new spots are always appearing wildly (Hanani, 2021). Therefore, this study aims to determine the role of the Tanjungpinang City Environment Agency in overcoming littering and its management. The method used to obtain data is the literature study method. The results showed that to deal with this waste problem, the Tanjungpinang City Government (Pemko) through the Environmental Agency distributed garbage cans and uniforms to the Waste Bank and Climate Village Programme (Proklim) from four sub-districts throughout Tanjungpinang City.